Improved Single Sign on Mechanism (International Journal of Engineering and Computer Science, 2014)
In this mechanisms allow users to sign on only once and have their identities automatically verified by each application or service they want to access afterwards. There are many practical and secure single sign-on models even though it is of great importance to current distributed application. Many application architectures required the user to memorized and utilize a different set of credentials (eg, username/password or tokens) for each application he/she wants permission. In this approach is not practical and not secure with the exponential growth in the number of applications and services a user has to access both inside corporative environments . This is a new authentication mechanism that enables a legal user with a single credential to be authenticated by multiple service providers in distributed computer networks. In this paper we proposed a new single sign-on scheme and claimed its security by providing well-organized security arguments. In this paper shows the Chang & Lee scheme and it aims to enhance security using RSA encryption and decryption. The programming part is done using socket programming in Java.Identification of user is an important access control mechanism for client–server networking architectures. The goal of a this  platform is to eliminate individual sign on procedures by centralizing user authentication and identity management at a central identity provider. In this paper a SSO the user should seamlessly authenticated to his multiple user accounts (across different systems) once he proves his identity to the identity provider